Optic nerve constraints for carbon ion RT at CNAO - Reporting and relating outcome to European and Japanese RBE - Dale, Jon Espen; Mairani, Andrea (Radiotherapy and oncology, 2019)
Background and purpose - Until now, carbon ion RT (CIRT) dose constraints for the optic nerve (ON) have only been validated and reported in the NIRS RBE-weighted dose (DNIRS). The aim of this work is to improve CNAO’s RBE-weighted dose (DLEM) constraints by analyzing institutional toxicity data and by relating it to DNIRS. - Material and methods - A total of 65 ONs from 38 patients treated with CIRT to the head and neck region in the period 2013-14 were analyzed. The absorbed dose (DAbs) of the treatment plans was reproduced and subsequently both DLEM and DNIRS were applied, thus relating CNAO clinical toxicity to DNIRS. - Results - Median FU was 47 (26-67) months. Visual acuity was preserved for the 56 ONs in which the old constraints were respected. Three ONs developed visual decline at DLEM|1% ≥71Gy(RBE)/DLEM|20% ≥68Gy(RBE), corresponding to DNIRS|1% ≥68Gy(RBE)/DNIRS|20% ≥62Gy(RBE). Dose recalculation revealed that NIRS constraints of DNIRS|1% ≤40Gy(RBE)/DNIRS|20% ≤28Gy(RBE) corresponded to DLEM|1% ≤50Gy(RBE)/DLEM|20% ≤40Gy(RBE). Reoptimization of treatment plans with these new DLEM constraints showed that the dose distribution still complied with NIRS constraints when evaluated in DNIRS. However, due to uncertainties in the method, and to comply with the EQD2-based constraints used at GSI/HIT, a more moderate constraint relaxation to DLEM|1% ≤45Gy(RBE)/DLEM|20% ≤37Gy(RBE) has been implemented in CNAO clinical routine since October 2018. - Conclusion - New DLEM constraints for the ON were derived by analyzing CNAO toxicity data and by linking our results to the experience of NIRS and GSI/HIT. This work demonstrates the value of recalculating and reporting results in both DLEM and DNIRS.